Systemic Risk : Simulating Local Shocks To A Global System - Scot A. C. Gould; Stephen A. Naftilan; Sarkis J. Khoury (Claremont McKenna College, Department of Economics, 2003)
Using our updated model of the payment exchange system within the banking industry, we have introduced sudden local economic shocks and calculated their effect on the stability of the financial system. Our results suggest that the probability of a total banking failure, i.e., the systemic risk of the system, is insignificant unless the degree of the shock and the degree of integration between banks are very large. We find that the larger the shock, i.e., the greater the amount of loss amongst all banks, and the more isolated banks are within the payment system, the greater the likelihood of a localized or global banking system failure. However, given the current limits percentages of capitol banks can loan each other, only worldwide economic crises of cataclysmic significance would cause a collapse of the entire banking system. Hence we affirm the findings of our previous work which considered the effects of a bank failure generated by factors internal to the banking system (internal instead of internal shocks), which suggest there is minimal systemic risk in an integrated, minimally regulated, banking system.
Keywords: G21; G1; 330; Finanzmarktkrise; Bankenkrise; Bankensystem; Zahlungsverkehr; Theorie